PENYIMPANGAN BERBAHASA PADA TATARAN MORFOLOGI DALAM TABLOID NYATA - Rustiati, Rustiati (Widya Warta, 2021)
This research aimed to determine language deviation at the morphology level in Nyata tabloids and their corrections. This research was qualitative descriptive research with data in the form of monomorphic and polymorphic words from Nyata tabloids published in February 2019. The results of this research were language deviations at morphology level included (1) the removal of affixes in the form of prefix removal and confix removal, (2) the replacement of morph that consisted of prefix and confix, and the abbreviated morph.